2003
DOI: 10.1159/000072403
|View full text |Cite
|
Sign up to set email alerts
|

Higher Content of 18:1 Trans Fatty Acids in Subcutaneous Fat of Persons with Coronarographically Documented Atherosclerosis of the Coronary Arteries

Abstract: Aim: To identify the total content of trans fatty acid (TFA) isomers and C18:1 trans isomers in subcutaneous fat samples from persons with atherosclerosis of the coronary arteries, as an indicator of dietary exposure. Methods: Using capillary gas chromatography, the authors determined total content of TFA isomers and C18:1 trans isomers in the subcutaneous fat of 34 patients with ischemic heart disease who had undergone aortocoronary bypass surgery and in 46 patients with no sign of coronary disease. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…However, in recent years, questions have been raised as to whether the consumption of linoleic acid has become excessive [20], to the point of actually contributing to an increased risk for coronary heart disease (CHD) via its conversion to arachidonic acid, the predominant substrate for proinflammatory prostaglandins, leukotrienes, thromboxane, and prostacyclin [21]. Dlouhy et al [22] demonstrated that higher linoleic acid intakes tend to decrease serum LDL-C levels, which cannot be explained by our results because the MG diet with lower linoleic acid content reveale a significant increase in LDL-C. It is assumed that industrial trans-fats increase LDL-C, which is confirmed in this study by the MG diet, which significantly increased LDL-C. Our findings clearly show that rats with hyperlipidemia induced by a high-fat feed exhibit trans-FA accumulation in their hearts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, questions have been raised as to whether the consumption of linoleic acid has become excessive [20], to the point of actually contributing to an increased risk for coronary heart disease (CHD) via its conversion to arachidonic acid, the predominant substrate for proinflammatory prostaglandins, leukotrienes, thromboxane, and prostacyclin [21]. Dlouhy et al [22] demonstrated that higher linoleic acid intakes tend to decrease serum LDL-C levels, which cannot be explained by our results because the MG diet with lower linoleic acid content reveale a significant increase in LDL-C. It is assumed that industrial trans-fats increase LDL-C, which is confirmed in this study by the MG diet, which significantly increased LDL-C. Our findings clearly show that rats with hyperlipidemia induced by a high-fat feed exhibit trans-FA accumulation in their hearts.…”
Section: Discussionmentioning
confidence: 99%
“…The other case control studies studied either C18:1 D9t isomer [31] or pooled all C18:1t isomers [32][33][34][35][36][37]. The C18:1t biomarker levels were not associated with risk in most of the studies [31][32][33][34][35], although one study reported that C18:1t levels were significantly higher [36] and another that they were significantly lower [37] in cases than in controls.…”
Section: Biomarkers Of Trans Fatty Acids Intake and Risk Of Coronary mentioning
confidence: 99%
“…TFA content in subcutaneous fat and in human milk fat is a good indicator of TFA dietary exposure. Dlouhý et al [14,15] have described TFA content in subcutaneous fat and in human breast milk fat in the general population of the Czech Republic. However, the intake of TFA in minor population groups that may differ due to specific eating habits has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%